The Impact Of E-Logistics On Firm Competitiveness : Case Study - OptakLogistics Pte Ltd. - K.G. Mani, Tamilarasan (2005)
Optak's business is both integrated logistics services and supply chain management.The research will undergo a detail study on how the local logistics firm deployed its e-logistics strategies. It is expected that the analysis of impact would further enhance the awareness among local logistics firm to realise and improve their service level.